Antibiotic therapy impact on intravesical BCG therapy efficacy for high-risk localized bladder cancer treatment - Aubert, Cécile; Culty, Thibaut; Zidane, Merzouka; Bigot, Pierre; Lebdai, Souhil (Frontiers in Oncology, 2024)
Intravesical Bacillus Calmettes-Guerin (BCG) instillations is the gold standard adjuvant treatment for high and very high-risk non-muscle-invasive bladder cancer (NMIBC).Antibiotics may be required to treat asymptomatic bacteriuria before instillations or to prevent side effects. By modifying the bladder microbiota and through its bactericidal action, it could modify the efficacy of BCG. This study evaluates the impact of antibiotics received during BCG-induction treatment on the oncological outcomes for high and very high risk NMIBC.We retrospectively included all patients who received a full induction regimen of BCG therapy between January 2017 and June 2022. Clinical and tumor characteristics as well as tolerability were collected. Recurrence-free survival (RFS) and progression-free survival (PFS) were compared according to the prescription of antibiotics, its type and duration.A total of 126 patients were included, 86.5% of the tumors were high risk and 13.5% very high risk. The median follow-up was 31 months (7-60). 36% of the patients received antibiotics during BCG-induction treatment (among which 44% received fluoroquinolones).There was no difference in RFS (p=0.902) or PFS (p=0.88) according to the duration or the type of antibiotics received. The use of a prolonged antibiotic treatment (> 7 days) significantly increased the duration of the BCG-induction treatment from 35 to 41,5 days (p=0,049) and the median number of delayed treatments by 1,5 [0-4]. Neither the use of antibiotics nor their duration modified the risk of recurrence or the intensity of side effects in multivariate analysis.Antibiotics received during BCG-induction immunotherapy did not influence oncological short-term outcomes or intensity of side effects.